2007
DOI: 10.1007/s00466-007-0203-9
|View full text |Cite
|
Sign up to set email alerts
|

A p-adaptive scaled boundary finite element method based on maximization of the error decrease rate

Abstract: This study enhances the classical energy norm based adaptive procedure by introducing new refinement criteria, based on the projection-based interpolation technique and the steepest descent method, to drive mesh refinement for the scaled boundary finite element method. The technique is applied to p-adaptivity in this paper, but extension to h-and hp-adaptivity is straightforward. The reference solution, which is the solution of the fine mesh formed by uniformly refining the current mesh, is used to represent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Consequently, ill-conditioned systems of the order 13 10 , such as found by selecting 1  in both analytical verification examples, were solved to the same level of accuracy as those with 6 10  . However, should the method be written without such solvers, care should be taken to avoid ill-conditioning by selecting an appropriate scaling factor, such that the terms in the influence matrices, H and G , are of the same order of magnitude.…”
Section: Matrix Scalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, ill-conditioned systems of the order 13 10 , such as found by selecting 1  in both analytical verification examples, were solved to the same level of accuracy as those with 6 10  . However, should the method be written without such solvers, care should be taken to avoid ill-conditioning by selecting an appropriate scaling factor, such that the terms in the influence matrices, H and G , are of the same order of magnitude.…”
Section: Matrix Scalingmentioning
confidence: 99%
“…This stress recovery technique and error estimator was used in conjunction with an h-hierarchical procedure to develop a simple h-adaptive mesh refinement strategy [12]. Vu and Deeks later developed a p-adaptive refinement procedure and showed that higher order shape functions in this adaptive technique offered improved convergence over h-adaptive methods [13,14]. Deeks developed a method of prescribing Dirichlet boundary conditions (displacement constraints) along side faces [15] and also demonstrated that the use of linear elements can give higher-order results on the undiscretised side faces.…”
Section: Introductionmentioning
confidence: 99%
“…This work was applied to a number of standard linear elasticity problems, and the technique was found to offer higher and better convergence than the original SBFEM. Furthermore, Vu and Deeks [11] presented a p-adaptive in the SBFEM for the two dimensional problem. These authors investigated an alternative set of refinement criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Although, the SBFEM has been successfully implemented in various applications, it also possesses certain drawbacks when the number of degrees of freedom resulting from the discretization becomes large, rendering the computational expenses substantial. To overcome such disadvantage, Vu and Deeks [30] integrated a p-adaptive scheme in the SBFEM for solving two dimensional boundary value problems. In this study, an alternative set of refinement criteria was considered to maximize the solution accuracy while minimizing the computational cost.…”
Section: Introductionmentioning
confidence: 99%